Governing metropolitan regions some approaches for Metro Manila - Oamar, Felipe V. (Philippine Journal of Public Administration, 1987)
Many approaches may be considered in trying to decide the most suitable administrative structure for a metropolitan area. These range from the creation of functional area-wide authorities to the return of some functions to the local government units to privatization of services. However, such approaches must prioritize the many urban functions that the metropolitan authority will be responsible for depending on the needs, and demands of the people in the area.